The Biceps and Superior Labrum Complex : A Clinical Casebook - Verma, Nikhil N.; Strauss, Eric J. (Springer International Publishing : Imprint: Springer, 2017)
Comprised exclusively of clinical cases covering the management of injuries to the biceps tendon and superior labrum, this concise, practical casebook will provide clinicians in orthopedics and sports medicine with the best real-world strategies to properly diagnose and treat the various types of injuries they may encounter. Each chapter is a case that opens with a unique clinical presentation, followed by a description of the diagnosis, assessment and management techniques used to treat it, as well as the case outcome and clinical pearls and pitfalls. Cases included illustrate different surgical management strategies for acute and chronic biceps tendon ruptures, anterior shoulder pain, subscapularis tears, proximal tenodesis, synovial chondromatosis and SLAP lesions type 1 through 4. Pragmatic and reader-friendly, The Biceps and Superior Labrum Complex: A Clinical Casebook will be an excellent resource for orthopedic surgeons, sports medicine practitioners and physical therapists alike.
Keywords: Medicine.; Orthopedics.; Sports medicine.; elektronické knihy; electronic books